OPTIMASI PENURUNAN KADAR ASAM DAN ANGKA PEROKSIDA MINYAK JELANTAH INDUSTRI KRECEK RAMBAK DENGAN KULIT SINGKONG - Desi Erlita (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
Cooking oil is one of basic food consumed by the whole society. One industry that many use a lot of cooking oil is krecek rambak industries at the Segoroyoso, Pleret, Bantul, Yogyakarta. One waste has not managed well in the rambak krecek industries is jelantah oil. The purpose of this research is to get cooking oil regenerate. The cooking oil regeneration done obtained from purification of jelantah oil using adsorbent (carbon active).One of the materials can be used as a carbon active is cassava skin. The skin cassava obtained from the waste of the merchant food. Making carbon active waste skin cassava done with chemicals process because the process simpler than with physics process. In this research, the longer time of submersion jelantah oil with adsorbent then the lesser levels of free fatty acids and peroxides in jelantah oil. The levels of free fatty acids and peroxide value optimally on the day to 6 submersion of 6,3835% and 15,6179Ml.eq/kg.